2019
DOI: 10.21037/jtd.2019.03.83
|View full text |Cite
|
Sign up to set email alerts
|

Detection, classification, and management of rejection after lung transplantation

Abstract: Rejection is a major complication following lung transplantation. Acute cellular rejection, lymphocytic bronchiolitis, and antibody-mediated rejection (AMR) are all risk factors for the subsequent development of chronic lung allograft dysfunction (CLAD). Acute cellular rejection and lymphocytic bronchiolitis have well defined histopathologic diagnostic criteria and grading. Diagnosis of AMR requires a multidisciplinary approach. CLAD is the major barrier to long-term survival following lung transplantation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 59 publications
0
54
0
Order By: Relevance
“…8 For this reason, it is methylprednisolone, but not dexamethasone, that has long been the clinically preferred steroid for an anti-inflammatory effect in lung diseases, such as in acute lung transplant rejection, pneumonitis in various autoimmune conditions, and drug toxicities. [8][9][10][11] A high dose of steroids is usually required in these conditions to achieve a direct effect on cell membrane-associated proteins. 13 Shorter duration of therapy can minimize side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 For this reason, it is methylprednisolone, but not dexamethasone, that has long been the clinically preferred steroid for an anti-inflammatory effect in lung diseases, such as in acute lung transplant rejection, pneumonitis in various autoimmune conditions, and drug toxicities. [8][9][10][11] A high dose of steroids is usually required in these conditions to achieve a direct effect on cell membrane-associated proteins. 13 Shorter duration of therapy can minimize side effects.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, it has been well established that among various corticosteroids, methylprednisolone, but not dexamethasone, is the clinically preferred agent for its antiinflammatory effect and high dose is required to achieve the therapeutic effect of the steroid. [8][9][10][11] As such, questions remain: Is the effect seen with dexamethasone drugspecific, or is it an anti-inflammatory effect of corticosteroid in general? If so, can sufficiently dosed methylprednisolone provide further benefit?…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation consisted in persistent, drug-resistant high fever. To the best of the authors’ knowledge, such severe hyperthermia associated to AMR has not being reported so far [ 5 ]. The diagnosis of lung AMR was especially difficult given both the atypical picture and the complexity of the global scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Rejection is a major complication during the development of PGD and CLAD, mainly including acute cellular rejection, antibody-mediated rejection, and chronic rejection [8] . Rejection is closely related to bronchiolitis obliterans syndrome, which represents a persistent obstructive decline in lung function and is regarded as an endpoint in most clinical studies [9] .…”
Section: Introductionmentioning
confidence: 99%